Hukum Persaingan Usaha dan Pembangunan Ekonomi di Indonesia - Cenuk Widiyastrisna Sayekti (Jurnal Hukum IUS QUIA IUSTUM, 2007)
This article illustrates the relationship between the role of law, especially competition law and economic development. Competition law is prerequisite of free market which gives us some advantages, including competitive price, increasing the quality of life and the social mobility, as well as efficiency both allocative and productive. Those advantages, however, only established if there are five qualities in law which render it conducive to economic development, such as stability, predictability, fairness, education, and special development abilities of law enforcer.